2017
DOI: 10.5194/npg-24-745-2017
|View full text |Cite
|
Sign up to set email alerts
|

Satellite drag effects due to uplifted oxygen neutrals during super magnetic storms

Abstract: Abstract. During intense magnetic storms, prompt penetration electric fields (PPEFs) through E × B forces near the magnetic equator uplift the dayside ionosphere. This effect has been called the "dayside super-fountain effect". Ionneutral drag forces between the upward moving O + (oxygen ions) and oxygen neutrals will elevate the oxygen atoms to higher altitudes. This paper gives a linear calculation indicating how serious the effect may be during an 1859-type (Carrington) superstorm. It is concluded that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Such signatures are consistent with either the global redistribution of high‐latitude Joule heating (see, e.g., Fuller‐Rowell et al., ; Oliveira et al., ; Richmond & Lu, ) or possibly from the direct uplift of the thermosphere through ion/neutral interactions as postulated by Tsurutani et al. () and Lakhina and Tsurutani (). However, as pointed by the latter authors, the last hypothesis has yet to be tested by nonlinear simulations that take into account the coupling between gravity, pressure gradients, viscosity, and advection of neutral atom flow effects, along with the heating and expansion during the uplift process.…”
Section: Statistical Resultssupporting
confidence: 78%
“…Such signatures are consistent with either the global redistribution of high‐latitude Joule heating (see, e.g., Fuller‐Rowell et al., ; Oliveira et al., ; Richmond & Lu, ) or possibly from the direct uplift of the thermosphere through ion/neutral interactions as postulated by Tsurutani et al. () and Lakhina and Tsurutani (). However, as pointed by the latter authors, the last hypothesis has yet to be tested by nonlinear simulations that take into account the coupling between gravity, pressure gradients, viscosity, and advection of neutral atom flow effects, along with the heating and expansion during the uplift process.…”
Section: Statistical Resultssupporting
confidence: 78%
“…Tsurutani et al () reported, for the Halloween event, ion‐neutral drag due to quick upward motion of O + that causes upward neutral oxygen (O) at equatorial latitudes. Similarly, Lakhina and Tsurutani () generalized the ion‐neutral drag for oxygen for 1859‐type (Carrington) superstorms. The O + outflow (higher latitudes) could have an impact on this ion‐neutral drag.…”
Section: Discussionmentioning
confidence: 99%
“…Because extremely strong MC magnetic fields are needed to produce extreme magnetic storms like the Carrington event Lakhina and Tsurutani, 2017), one should focus on extremely fast events for forecasting purposes. The geoeffective interplanetary dawn-to-dusk electric field is |V sw × B south |.…”
Section: Forecasting Magnetic Storms and Extreme Storms Associated Wimentioning
confidence: 99%